Return to running for postpartum elite and subelite athletes - Woodroffe, L.; Slayman, T.; Paulson, A.; Kruse, N.; Mancuso, A. (Sports Health: A Multidisciplinary Approach, 2024)
Context There is little evidence to guide elite athletes who desire returning to competition after giving birth to a child. Ultimately, this can result in decreased performance and increased risk of injury. This paper addresses aspects that must be considered when building and monitoring a return to running program for a postpartum elite or subelite athlete, including pelvic floor and core stability, progressive reloading of the musculoskeletal system, monitoring of nutritional parameters, and considerations for lactation.